CRISPR-based knockout screening identifies the loss of MIEF2 to enhance oxaliplatin resistance in colorectal cancer through inhibiting the mitochondrial apoptosis pathway - Xie, Chaozheng; Li, Kang; Li, Ya; Peng, Xudong; Teng, Biyun; He, Kuan; Jin, Aishun; Wang, Wang; Wei, Zhengqiang (Frontiers in Oncology, 2022)
The first-line anticancer agent oxaliplatin (OXL) is the preferred drug for treating colorectal cancer (CRC); however, the development of drug resistance is common in patients treated with OXL, which considerably reduces the efficacy of OXL-based regimens. By performing genome-wide CRISPR/Cas9 library knockdown screening, we found that mitochondrial elongation factor 2 (MIEF2) was among the top candidate genes. The OXL-resistant cell lines and organoids developed in the present study showed stable but low expression of MIEF2. Reduced MIEF2 expression may enhance CRC resistance to OXL by reducing mitochondrial stability and inhibiting apoptosis by decreasing cytochrome C release. In conclusion, among the different biomarkers of OXL resistance in CRC, MIEF2 may serve as a specific biomarker of OXL responsiveness and a potential target for the development of therapies to improve chemotherapeutic effectiveness.